Effect of oestradiol and progesterone replacement on bronchopulmonary dysplasia in extremely preterm infants. Issue 2 (11th August 2006) - Trotter, A; Maier, L; Kron, M; Pohlandt, F
Abstract : Objective: To study whether postnatal replacement of oestradiol and progesterone may help to prevent bronchopulmonary dysplasia (BPD). Methods: This randomised placebo-controlled double-blind study enrolled 83 infants of <29 weeks gestational age and 1000 g birth weight requiring mechanical ventilation within 12 h after birth. Oestradiol (2.5 mg/kg/day) and progesterone (22.5 mg/kg/day) were given by continuous intravenous infusion of a standard lipid emulsion (15 ml/kg/day) in the replacement group (ESTRA-PRO). The placebo group received the same lipid emulsion without oestradiol or progesterone. A replacement period of at least 2 weeks but not >4 weeks was strived for and defined as "according to protocol". The primary outcome variable was the incidence of BPD or death. Results: The median birth weight was 670 g (min–max 400–990 g) and the gestational age 25 weeks (23.1–28.1 weeks). The incidence of BPD or death was 48% in the placebo group and 44% in the ESTRA-PRO group (p = 0.38, one-sided testing, intention to treat analysis). In infants treated according to protocol, 32% (9 of 28) in the placebo group and 14% (3 of 21) in the ESTRA-PRO group developed BPD (p = 0.08). Conclusion: Replacement of oestradiol and progesterone was not effective for prevention of BPD or death in extremely preterm born infants. Better-powered trials are needed to evaluate this new approach.